Mapping the tumor microenvironment in bladder cancer and exploring the prognostic genes by single-cell RNA sequencing - Chen, Zhibin; Chen, Dongmao; Song, Zhenfeng; Lv, Yifan; Qi, Defeng (Frontiers in Oncology, 2023)
Despite substantial advances in the treatment of immune checkpoint inhibitor (ICI), the clinical expected therapeutic effect in the matter of bladder cancer has not been achieved, in which the tumor microenvironment (TME) occupies a notable position. In this research, 10X single-cell RNA sequencing technology was conducted to analysis on 7 primary bladder tumor tissues (3 NMIBC,4 MIBC) and 7 corresponding normal tissues adjacent to cancer, we identify 8 various cell types in the BC TME, and made a complete TME atlas in bladder cancer. Besides, we further subdivided bladder cancer epithelial cells into 14 subgroups, indicating a high intra-tumoral heterogeneity. Additionally, we compared the differences between NMIBC and MIBC based on differential gene expression heat map, CNV distribution heat map, GO enrichment analysis and KEGG enrichment analysis. WGCNA and PPI protein network mutual analysis and Kaplan-Meier survival prognosis analysis were used to identify 6 key genes associated with the prognosis of bladder cancer: VEGFA, ANXA1, HSP90B1, PSMA7, PRDX6, PPP1CB. The dynamic change of the 6 genes expression distribution on the pseudo-time axis was further verified by cell pseudo-time analysis.